Augmented Reality-Based E-Module for Virtual Field Trips to Enhance Spatial Thinking and Problem-Solving - Muhammad Fathul Fuadi; Wasino (Universitas Negeri Malang, 2026)
Abstract: This study aimed to develop and validate an augmented reality (AR)-based e-module incorporating virtual field trips (VFTs) to improve spatial thinking and problem-solving skills in elementary science education. Utilizing a Research and Development (R&D) methodology guided by the ADDIE model, the research involved 64 fifth-grade students divided into experimental and control groups. Data were gathered through spatial thinking and problem-solving assessments, observation checklists, and student feedback surveys, and subsequently analyzed using ANCOVA. The results demonstrated that the experimental group significantly outperformed the control group (p < .05). Qualitative feedback further revealed enhanced student engagement, visualization capabilities, and conceptual understanding. The primary contribution of this study is its demonstration of how integrating AR with VFTs advances existing learning theories by connecting embodied visualization with inquiry-based problem-solving. The novelty of this research lies in applying AR-enhanced VFTs within elementary science education in resource-limited settings, where opportunities for real-world field experiences are scarce. Beyond the local context, these findings contribute to the global discourse on utilizing immersive technologies to cultivate essential 21st-century skills, particularly spatial reasoning and problem-solving, which are vital across STEM education worldwide. Abstrak: Penelitian ini bertujuan untuk mengembangkan dan memvalidasi modul e-learning berbasis augmented reality (AR) yang mengintegrasikan kunjungan lapangan virtual (VFT) untuk meningkatkan kemampuan berpikir spasial dan pemecahan masalah dalam pendidikan sains tingkat dasar. Menggunakan metodologi Penelitian dan Pengembangan (R&D) yang didasarkan pada model ADDIE, penelitian ini melibatkan 64 siswa kelas lima yang dibagi menjadi kelompok eksperimen dan kelompok kontrol. Data dikumpulkan melalui penilaian pemikiran spasial dan pemecahan masalah, daftar periksa observasi, dan survei umpan balik siswa, dan kemudian dianalisis menggunakan ANCOVA. Hasil menunjukkan bahwa kelompok eksperimen secara signifikan outperformed kelompok kontrol (p < .05).Umpan balik kualitatif lebih lanjut mengungkapkan peningkatan keterlibatan siswa, kemampuan visualisasi, dan pemahaman konseptual. Kontribusi utama studi ini adalah demonstrasinya tentang bagaimana integrasi AR dengan VFTs memperkaya teori pembelajaran yang ada dengan menghubungkan visualisasi yang tertanam dengan pemecahan masalah berbasis penyelidikan. Keunikan penelitian ini terletak pada penerapan VFTs yang diperkaya AR dalam pendidikan sains dasar di lingkungan dengan sumber daya terbatas, di mana kesempatan untuk pengalaman lapangan di dunia nyata jarang tersedia. Di luar konteks lokal, temuan ini berkontribusi pada diskusi global tentang penggunaan teknologi imersif untuk mengembangkanketerampilan abad ke-21 yang esensial, terutama penalaran spasial dan pemecahan masalah, yang vital dalam pendidikan STEM di seluruh dunia.